2019
DOI: 10.1038/s41598-019-38710-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome transmission in BC4 progenies of intergeneric hybrids between Saccharum spp. and Erianthus arundinaceus (Retz.) Jeswiet

Abstract: Intergeneric hybrids between Saccharum spp. and Erianthus arundinaceus and clones derived from these hybrids and backcrosses to Saccharum spp. were used to study the transmission of E . arundinaceus chromosomes by genomic in situ hybridization (GISH). True hybrid progenies were precisely identified using PCR with a primer pair, AGRP52/53. The results showed that AGRP52/53 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…In particular, a comprehensive analysis with common DNA markers targeting Erianthus accessions collected in Asian countries, where the genetic resources are plentiful, would not only clarify the position of the Thai germplasms, but also provide information on genetic characteristics of the available resources of Erianthus species. This knowledge would allow efficient maintenance and conservation of the genetic resources of these species of large grasses and would facilitate the use of Erianthus species as breeding materials for the development of novel bioenergy crops and the improvement of sugarcane, which is now in progress in some countries [ 11 , 15 , 43 , 44 ]. Such studies might be an important step toward mitigation of and adaptation to global warming.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a comprehensive analysis with common DNA markers targeting Erianthus accessions collected in Asian countries, where the genetic resources are plentiful, would not only clarify the position of the Thai germplasms, but also provide information on genetic characteristics of the available resources of Erianthus species. This knowledge would allow efficient maintenance and conservation of the genetic resources of these species of large grasses and would facilitate the use of Erianthus species as breeding materials for the development of novel bioenergy crops and the improvement of sugarcane, which is now in progress in some countries [ 11 , 15 , 43 , 44 ]. Such studies might be an important step toward mitigation of and adaptation to global warming.…”
Section: Discussionmentioning
confidence: 99%
“…Our result agrees with other studies that used AFLP [78,79], cpSSR [80], TRAP [21,30,59], SRAP [55] and SSR [3,81] markers. The introgression of alleles of the Erianthus genus in sugarcane breeding programs, mainly from E. arundinaceus, has been evaluated in recent years to increase adaptability, disease resistance, drought resistance and biomass production [82,83]. Despite this, further studies may be conducted to evaluate other regions of the genome closely related to the outstanding traits of the Erianthus genus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, E. arundinaceum was referred to T. arundinaceum accordingly. Currently, many studies have reported cytogenetic research on T. arundinaceum, especially on the chromosome inheritance of the hybrids between sugarcane and T. arundinaceum [4][5][6]. However, basic cytogenetic information such as the karyotype, and the precise chromosome contribution of T. arundinaceus in interspecific hybridization, could not be addressed due to lack of effective cytogenetic markers to identify the individual chromosomes.…”
Section: Introductionmentioning
confidence: 99%